Kontra-Radikalisasi Berbasis Media Sosial sebagai Instrumen Pencegahan Terorisme : Analisis Hukum terhadap Penguatan Instrumen dan Struktur BNPT - Nur Raima Hafizhah; Rildo Anuar Sihite; Slamet Tri Wahyudi (International Forum of Researchers and Lecturers, 2025)
The increasingly massive development of social media has been exploited by terrorist groups as a strategic tool to spread propaganda, violent ideology, and radicalism to the wider community, especially the younger generation. This situation demands an effective counter-radicalization strategy that adapts to the dynamics of the digital space. This study aims to analyze the strengthening of legal instruments and the role and institutional structure of the National Counterterrorism Agency (BNPT) in implementing social media-based counter-radicalization policies. The research method used is a normative juridical approach with a legislative approach and a conceptual approach, through a review of laws and regulations, legal doctrine, and policies related to counter-terrorism in Indonesia. The results show that the normative legal basis for BNPT's authority to carry out counter-radicalization is already available, particularly in the Law on the Eradication of Criminal Acts of Terrorism. However, its implementation still faces various obstacles, including weak derivative regulations specifically governing the supervision and counter-measures of digital radicalism, limited inter-agency coordination, and suboptimal evaluation of data- and technology-based policies. Therefore, this study recommends strengthening derivative regulations, increasing the digital capacity of BNPT, and developing a more integrated coordination and evaluation system.